2006
DOI: 10.1364/ao.45.003991
|View full text |Cite
|
Sign up to set email alerts
|

Apparent violation of the radiant exposure reciprocity law in interline CCDs

Abstract: We analyze in detail the apparent violation of the reciprocity law that occurs for an interline CCD array owing to its responsivity that varies with exposure time, and we investigate other parameters having an influence on this variation, such as the numerical aperture of the system or the illumination wavelength. The variation can be explained from a qualitative point of view by the charge leakage that occurs from the sense region to the register region during readout time. This change of the responsivity can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Nonetheless, results proved that responsivity was also affected by the integration-time set. This phenomenon had been previously reported in a CCD imager sensor [3]. In both cases, it was concluded that the phenomenon was due to the leakage of photo-generated electrons in the photodiode during the readout phase; these electrons would be added to those generated during the integration time.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Nonetheless, results proved that responsivity was also affected by the integration-time set. This phenomenon had been previously reported in a CCD imager sensor [3]. In both cases, it was concluded that the phenomenon was due to the leakage of photo-generated electrons in the photodiode during the readout phase; these electrons would be added to those generated during the integration time.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, in pixel 32 any fitting that took into account the different error bars would led to an almost constant L norm curve within the whole integration-time range. A relationship between responsivity and the integration time had been previously reported [3] in CCD detectors. Since light is not blocked during the readout phase, the phenomenon could be explained by the leakage of a significant amount of electrons during this phase due to pixel irradiation.…”
Section: Nonlinearity Characterizationmentioning
confidence: 73%
See 2 more Smart Citations
“…In turn, non-linearities related with the integration time affected also the characterization of other instrumental artifacts . This dependence, previously reported in cameras (Ferrero et al, 2006) but not in field spectroradiometers, is significant when the integration time is close to the readout time of the sensor (i.e. a photodiode continues to collect photons during the time when the signal is being processed (the readout time), producing an extra signal that is added to that obtained during the integration time).…”
Section: Linearity Of Spectrometer Responsementioning
confidence: 80%